A hydrometallurgical process for the recovery of cerium from Khuren khad ore (Proceedings of the Mongolian Academy of Sciences, 2019)
This study presents the recovery of cerium (Ce) from Khuren Khad ore by using the hydrometallurgical process. Several methods of leaching and precipitation were employed to investigate the recovery efficiency of Ce from the ore. According to the result, it is 4.8% of Ce contained in this ore sample. The best result of this study reveals that 100% Ce leaching efficiency can be obtained under leaching conditions of 6N HCl at a temperature of 70° C and 5g/50mL solid/liquid ratio and 3h. Further, 99.60% precipitation recovery of Ce was achieved with NaHCO3 at an interval of 24 hours. After leaching and precipitation, the concentration of Ce was enriched from 4.8% of Khuren Khad ore to 33.09% of precipitation product.